2015
DOI: 10.1111/1750-3841.13131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radio Frequency, Microwaving, and High Hydrostatic Pressure at Elevated Temperature on the Nutritional and Antinutritional Components in Black Soybeans

Abstract: In this study, the effects of high hydrostatic pressure (HHP) at elevated temperature (60 °C) and 2 dielectric heating (DH) methods (radio frequency [RF], and microwaving [MW]) on the nutritional compositions and removal of antinutritional factors in black soybeans were studied. Each treatment caused <2% reduction in protein, and 3.3% to 7.0% decline in total amino acid content. However, the proportion of essential amino acid slightly increased in DH treated samples. The treatment decreased fat content (14.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The intensity of the peaks at 1645 cm −1 and 2800–3000 cm −1 decreased in the samples, which may be due to a decrease in the triglycerides and protein contents. Zhong et al [ 35 ] reported similar results of a reduction in lipid and protein contents (%) after RF treatment. The peaks in the FTIR spectrum could also be related to the creation of melanoidins during the RF heating process [ 33 ].…”
Section: Resultsmentioning
confidence: 69%
“…The intensity of the peaks at 1645 cm −1 and 2800–3000 cm −1 decreased in the samples, which may be due to a decrease in the triglycerides and protein contents. Zhong et al [ 35 ] reported similar results of a reduction in lipid and protein contents (%) after RF treatment. The peaks in the FTIR spectrum could also be related to the creation of melanoidins during the RF heating process [ 33 ].…”
Section: Resultsmentioning
confidence: 69%
“…Long‐time treatments under high temperature inevitably cause the cracks or hard shells in the final products induced by surface overheating and dehydration. To minimise the unfavourable effects, some heating techniques, such as microwave treatment (Zhong et al , 2015) and infrared treatment (Yalcin & Basman, 2015), have been applied to improve the product quality. While available studies have proved the effectiveness of these heating techniques, the phenomena of surface overheating and dehydration still exist in large volume products due to their poor penetration depth.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest RF treatment could inactivate ANFs in soaked soybean (Zhong et al , 2015). However, its application results in considerable quantities of waste water and short shelf life induced by bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency energy is non-ionizing radiations emitted at a frequency that is not strong enough to cause ionization of atoms and molecules 7,8. The biological effects related to RF exposure are divided into three levels: 1) interaction with biological macromolecular structures without clinical effects;9 2) reversible morphological and functional modifications in macromolecular structures with instrumentally, clinically or subjectively demonstrable effects that quickly disappear upon cessation of the stimulus;10 and 3) permanent biological damage that does not disappear upon cessation of the stimulus, wherein the biological effects exceed efficacy thresholds of damage repair, adaptation, and compensatory mechanisms 11…”
Section: Introductionmentioning
confidence: 99%